Outcomes and lessons learnt from practice of retrograde intrarenal surgery (RIRS) in a paediatric setting of various age groups: a global study across 8 centres - ŞEKERCİ, ÇAĞRI AKIN; TANIDIR, YILÖREN (My University, 2022)
Purpose To analyse and report the practice, outcomes and lessons learnt from a global series of retrograde intrarenal surgery (RIRS) in a paediatric multicentre series. Methods A retrospective review of anonymized pooled data gathered globally from 8 centres in paediatric patients ( 10 years (Group C). Overall, post-operative complication rate was 13.7%. Chi-square comparisons were used for categorical variables; analysis of variance (ANOVA) or Kruskal-Wallis tests were used for continuous variables. Results 314 patients were analysed. The mean age was 9.54 +/- 4.76 years. Groups A, B and C had 67 (21.3%), 83 (26.4%) and 164 (52.2%) patients, respectively. Mean stone size was 10.7 +/- 4.62 mm. Pre-stenting was performed in 155 (49.4%) of patients, ureteral access sheaths (UAS) was used in 54.5% of patients with majority (71%) utilizing holmium laser for stone fragmentation. All complications were minor (Clavien-Dindo grade 1 and 2). SFR was 75.5%. Conclusions RIRS is acceptable as a first-line intervention in the paediatric population with reasonable efficacy and low morbidity. Complications are slightly higher in patients < 5 years of age, which should be taken into account while counselling patients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Urology; Paediatric; Renal stone; Retrograde intrarenal surgery; Ureteroscopy; Renal calculi; STONE DISEASE; URETEROSCOPY; ACCESS